2020
DOI: 10.1038/s41467-020-15856-y
|View full text |Cite
|
Sign up to set email alerts
|

The vaginal microbiota associates with the regression of untreated cervical intraepithelial neoplasia 2 lesions

Abstract: Emerging evidence suggests associations between the vaginal microbiota (VMB) composition, human papillomavirus (HPV) infection, and cervical intraepithelial neoplasia (CIN); however, causal inference remains uncertain. Here, we use bacterial DNA sequencing from serially collected vaginal samples from a cohort of 87 adolescent and young women aged 16-26 years with histologically confirmed, untreated CIN2 lesions to determine whether VMB composition affects rates of regression over 24 months. We show that women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
159
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(170 citation statements)
references
References 82 publications
(92 reference statements)
11
159
0
Order By: Relevance
“…Therefore, further studies investigating the involvement of the metabolites from Methyloversatilis in the growth and the metabolism of cancer cells may explain its association with prognosis and would be a stepping-stone for the understanding of HNCs. In accordance with previous studies of vaginal microbiota, Lactobacillus, asscociated with the early regressions of cervical intraepithelial neoplasia [39], was found associated with good prognosis of HNCs in our study. Together with the essential role of Lactobacillus in the balance of microbiota, the ndings suggested that Lactobacillus depletion and microbial dysbiosis by antibiotic abuse in clinic might associate with poor prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, further studies investigating the involvement of the metabolites from Methyloversatilis in the growth and the metabolism of cancer cells may explain its association with prognosis and would be a stepping-stone for the understanding of HNCs. In accordance with previous studies of vaginal microbiota, Lactobacillus, asscociated with the early regressions of cervical intraepithelial neoplasia [39], was found associated with good prognosis of HNCs in our study. Together with the essential role of Lactobacillus in the balance of microbiota, the ndings suggested that Lactobacillus depletion and microbial dysbiosis by antibiotic abuse in clinic might associate with poor prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…Our ndings suggest that women planned for CIN treatment had signi cantly higher levels of a high diversity, Lactobacillus spp.-depleted microbiome pre-treatment compared to a healthy, untreated control group with normal cytology. This nding is in line with previously published cross-sectional data describing associations between the VMB and the presence of CIN [4,8,14,15] with Atopobium, Sneathia, and Prevotella species being consistently associated with higher-grade disease across studies [4,6,8,14,41], the latter two of which were signi cantly overrepresented in our pre-treatment cohort compared to controls. Our analysis further revealed that excision of CIN does not impact on the VMB composition six months after treatment, which remained more diverse with a decreased relative abundance of Lactobacillus crispatus compared to normal controls.…”
Section: Discussionsupporting
confidence: 93%
“…depletion is associated with higher rates of persistent/progressive CIN2 at 12 and 24-month follow-up, whilst Lactobacillus spp. dominance associated with increased rates of regression [6].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, much less is known about the role of lectins in shaping microbial niches in the lower female reproductive tract, which play a key role in shaping health and disease throughout a woman's life span (MacIntyre et al, 2017). Colonisation in the vagina by Lactobacillus species has for long been considered a hallmark of health (Ma et al, 2012;van de Wijgert et al, 2014), whereas Lactobacillus deplete, high diversity vaginal microbiomes enriched in potential pathogens are characteristic of bacterial vaginosis and are associated with increased risk of sexually transmitted infections (STIs) (Borgdorff et al, 2014;Reimers et al, 2016), progression of cervical cancer (Mitra et al, 2020) and adverse pregnancy outcomes such as miscarriage and preterm birth (Al-Memar et al, 2019;Brown et al, 2019;Fettweis et al, 2019;Kindinger et al, 2016). A key component of the vaginal mucosa are highly glycosylated mucins that are derived from the mucin-secreting glands of the cervix (Gipson, 2001).…”
Section: Introductionmentioning
confidence: 99%